2008
DOI: 10.1029/2007jd008777
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal gravity wave activity observed with the Equatorial Atmosphere Radar and its relation to rainfall information from the Tropical Rainfall Measuring Mission

Abstract: [1] Five years of tropospheric data below 12 km from the Equatorial Atmosphere Radar (EAR) are examined for seasonal and interannual gravity wave activity. Results are compared with data from the Tropical Rainfall Measuring Mission (TRMM) satellite. A semiannual cycle of vertical wind variances inside and above convection is found. Maxima occur at the equinoxes and minima at the solstices. This semiannual cycle is also observed in the TRMM storm height and surface rainfall. Half of the vertical wind variance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…2 was suppressed in 2002/2003 and 2004/2005, which seem to be a result of the wave-mean flow interaction with the QBO, as reported by de la Torre et al (2006), who also used CHAMP GPS RO data. A comparable interaction was also reported by Sato and Dunkerton (1997) using routine radiosonde soundings at Singapore.…”
Section: Seasonal Variations Of E P In 2001-2006mentioning
confidence: 56%
See 2 more Smart Citations
“…2 was suppressed in 2002/2003 and 2004/2005, which seem to be a result of the wave-mean flow interaction with the QBO, as reported by de la Torre et al (2006), who also used CHAMP GPS RO data. A comparable interaction was also reported by Sato and Dunkerton (1997) using routine radiosonde soundings at Singapore.…”
Section: Seasonal Variations Of E P In 2001-2006mentioning
confidence: 56%
“…In DJF, the centers are north-east of Papua New Guinea and between Borneo and Sumatra islands; in MAM, however, the entire pattern seems to be slightly shifted south-westward so that enhanced E p is east of Borneo and west of Sumatra. Alexander et al (2008) analyzed the seasonal variations of gravity wave activity using tropospheric wind data collected with equatorial atmosphere radar (EAR) at Koto Ta- of E p from the zonal mean is also averaged for 5 years (right). From top to bottom, the panels show the results every 3 months in June-July-August, September-October-November, December-January-February, and March-April-May, respectively.…”
Section: Climatological Distribution Of E Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the GW variance alone cannot tell whether wave-mean flow interaction is taking place or not (which requires divergence of momentum flux), here we try to understand what causes such a good correlation between the two, considering that the GWs are contributing to the MSAO. Alexander et al (2008) have shown that the GW variance in the troposphere has a seasonal variation, with the variance being more during equinoxes and less during solstices. Thus, more GWs are generated during equinoxes and less during solstices.…”
Section: Discussionmentioning
confidence: 99%
“…Dutta et al, 2009;Alexander et al, 2008b) and in the MLT region (e.g. Kovalam et al, 2006;Taylor et al, 2009).…”
Section: Introductionmentioning
confidence: 99%